THE ISSUES AND CHALLENGES OF MATHEMATICS TEACHING AND LEARNING IN MALAYSIA ORANG ASLI PRIMARY SCHOOLS FROM TEACHERS' PERSPECTIVES (Malaysian Journal of Learning and Instruction, 2021)
Purpose - The Malaysian government has allocated a large budget for Orang Asli primary school education via the Department of Orang Asli Development (JAKOA) to help improve Orang Asli pupils’ academic performance including mathematics. Teachers face challenges in ensuring that Orang Asli pupils become competent learners of mathematics. Hence, this study examined the teachers’ perspectives on the issues and challenges in the teaching and learning of mathematics at Orang Asli primary schools in Malaysia. Methodology - In this qualitative study, Two Orang Asli primary schools were randomly selected from eight primary schools within an Orang Asli Settlement in the District of Sungai Siput. The data were collected via focus group discussions and interviews, which were carried out during enculturation visits and were fully transcribed and thematically analysed. The research participants were purposively selected and comprised the schools’ administrators and mathematics teachers. Findings - The results of the data analysis showed that there were two main themes, namely classroom challenges and school challenges, in determining mathematics competence among Orang Asli pupils. Classroom challenges consisted of five sub-themes namely coverage of mathematics syllabus, mathematics teaching and learning resources, pupil engagement, language barrier, and mathematics learning culture. School challenges consisted of two sub-themes namely school attendance and discipline. To enhance mathematics competence among Orang Asli pupils, it is deemed important to conduct programmes and community engagement. Significance - This study contributes to the knowledge of the teaching and learning of mathematics at Orang Asli primary schools. It is recommended that teachers allow Orang Asli pupils to take home their mathematics textbooks so that they can complete their homework at home. Teachers are highly encouraged to conduct mathematics teaching and learning activities in groups to develop meaningful and engaging lessons.